Disseminierte intravasale Gerinnung, Perimyokarditis und bilaterales Pleuraempyem bei adultem Still-Syndrom = Disseminated intravascular coagulation, perimyocarditis and bilateral pleural empyema in adult Still's disease - Krzossok, Stefan; Benck, Urs Tobias; Woude, Fokko J. van der; Braun, Claude (Deutsche medizinische Wochenschrift, 2004)
HISTORY: A 21-year-old man was admitted to the hospital because of high fever, arthralgias and myalgias. One week before he was treated with penicillin G orally because of cough and sore throat. PHYSICAL EXAMINATION: The critically ill patient presented with a red throat and cervical lymphadenopathy. Lung auscultation revealed reduced respiratory sounds at both base, heart auscultation revealed a pericardial friction rub. Dermatologic examinations were normal. INVESTIGATIONS: Laboratory findings were notable for anemia, thrombopenia and leukocytosis, disseminated intravascular coagulation and markedly elevated CRP (309 mg/l). Electrogram showed inferior and lateral ST segment depression. Echocardiography showed pericardial effusion. Chest CT scan revealed bilateral pleural effusion, a left-sided small infiltrate and enlarged mediastinal lymph nodes. Abdominal ultrasound confirmed hepatosplenomegaly and ascites. TREATMENT AND CLINICAL COURSE: A diagnosis of parapneumonic bilateral pleural empyema, perimyocarditis and disseminated intravascular coagulation was made. Despite institution of empiric antibiotic therapy, no clinical improvement was observed. After exclusion of infectious, autoimmune or malignant disease, clinical and laboratory data, especially marked hyperferritinemia, helped to establish the diagnosis of adult-onset Still's disease. Immunosuppressive treatment with prednisolone and azathioprin resulted in remission. CONCLUSION: Adult-onset Still's disease is a rare inflammatory disorder of unknown origin, which may affect multiple organs. The diagnosis is based on a diagnostic score, which includes a number of clinical and laboratory findings, published by Yamaguchi in 1992. Marked hyperferritinemia represents an additional diagnostic clue to the disease.